Developmental integration in a functional unit: deciphering processes from adult dental morphology. Issue 4 (July 2014) - Labonne, Gaëlle; Navarro, Nicolas; Laffont, Rémi; Chateau‐Smith, Carmela; Montuire, Sophie
SUMMARY The evolution of mammalian dentition is constrained by functional necessity and by the non‐independence of morphological structures. Efficient chewing implies coherent tooth coordination from development to motion, involving covariation patterns (integration) within dental parts. Using geometric morphometrics, we investigate the modular organization of the highly derived vole dentition. Integration patterns between and within the upper and lower molar rows are analyzed to identify potential modules and their origins (functional and developmental). Results support an integrated adult dentition pattern for both developmental and functional aspects. The integration patterns between opposing molar pairs suggest a transient role for the second upper and lower molars during the chewing motion. Upper and lower molar rows form coherent units but the relative integration of molar pairs is in contradiction with existing developmental models. Emphasis on the first three cusps to grow leads to a very different integration pattern, which would be congruent with developmental models. The early developmental architecture of traits is masked by later stages of growth, but may still be deciphered from the adult phenotype, if careful attention is paid to relevant features.